Effects of Task-Based LSVT-BIG Intervention on Hand Function, Activity of Daily Living, Psychological Function, and Quality of Life in Parkinson’s Disease: A Randomized Control Trial - YoungSeok Choi; DeokJu Kim (Occupational Therapy International)
Previous studies have demonstrated that the Lee Silverman Voice Treatment-BIG (LSVT-BIG) program can improve motor functions such as balance and gait in Parkinson’s disease (PD) patients. However, no study has investigated the effects of a task-based LSVT-BIG intervention on hand function, psychological function, and quality of life in PD patients. Herein, we investigate the effects of a task-based LSVT-BIG intervention, which reflects the needs of PD patients, on hand function, activity of daily living (ADL), psychological function, and quality of life. A total of 14 PD patients were enrolled and randomly assigned to the experimental or control group. The experimental group performed 30 minutes of conventional occupational therapy and 40 minutes of the task-based LSVT-BIG program. The control group performed 30 minutes of conventional occupational therapy and 40 minutes of relaxation and stretching. Both groups underwent the respective interventions once a day 5 times a week for 4 weeks. As a result of the study, the experimental group showed improvement in hand function in both the dominant and nondominant hand, and the control group showed improvement only in the nondominant hand (p<.05). ADL was significantly improved in both groups, but the experimental group showed a more statistically significant difference than the control group (p<.05). Depression and anxiety were significantly decreased in both the experimental group and the control group, and in particular, in the case of anxiety, there was a more statistically significant difference in the experimental group (p<.05). In the case of the experimental group, there was a significant improvement in quality of life in all items, and in the control group, except for the social function item (p>.05), there was a significant improvement in other items (p<.05). The results of this study suggest that the task-based LSVT-BIG program, which consists of activities desired by the participants, may be an effective intervention to improve hand function, ADL, psychological function, and quality of life in PD patients.